2006
DOI: 10.1080/09593332708618643
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Biomass in a Hybrid MBBR Reactor

Abstract: The structural features of biomass present in the hybrid MBBR (Moving Bed Biofilm Reactor) aeration tank were studied in two subsequent periods, which differed in hydraulic and substrate loads. The physical characteristics of attached-growth biomass, such as, biofilm thickness, density, porosity, inner and surface fractal dimensions, and those of suspended-growth biomass, such as, floc size distribution, density, porosity, inner and surface fractal dimensions, were investigated in each study period and then co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The higher biomass loading -the higher attached biomass concentration (the same -lower suspended biomass concentration). This phenomenon was also observed by other authors [26]. The elevated pH caused the ammonia release and inhibition of the second phase of nitrification and this way the total nitrogen removal process was shorten by elimination of two elementary processes: nitratation and denitratation ( figure 8).…”
Section: Carbon and Nitrogen Compounds Removal Efficiency In Continuosupporting
confidence: 62%
See 2 more Smart Citations
“…The higher biomass loading -the higher attached biomass concentration (the same -lower suspended biomass concentration). This phenomenon was also observed by other authors [26]. The elevated pH caused the ammonia release and inhibition of the second phase of nitrification and this way the total nitrogen removal process was shorten by elimination of two elementary processes: nitratation and denitratation ( figure 8).…”
Section: Carbon and Nitrogen Compounds Removal Efficiency In Continuosupporting
confidence: 62%
“…Some authors indicated that in continuous-flow MBBR in which SND process was established, the microbial community structures of biofilm are related to C/N ratios [25]. In MBBRs the volume concentration ratio of biofilm to the activated sludge flocs cab be even higher: 5-13 [26] than for separated attached biomass and suspended biomass systems. Some important differences between biofilm and flocs features in MBBRs were found by Xiao end Garnczarczyk [26].…”
Section: Spatial and Ecological Forms Of Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that it was desirable to maintain an influent formaldehyde concentration lower than 202.2 mg/L, as this concentration could achieve a good biofilm morphology while not inhibiting its microbial activity. The structural features of biomass present in the hybrid moving bed biofilm reactor (MBBR) aeration tank were studied in two subsequent periods, which differed in hydraulic and substrate loads (Xiao and Ganczarczyk, 2006). The results indicated that biofilm always had a higher density, geometric porosity, and a larger boundary fractal dimension than flocs.…”
Section: Factors Affecting Biofilm Structures Andmentioning
confidence: 99%
“…The MBBR reactor volume has no unused space, an advantage of having the biofilm reactors totally mixed. MBBR has a great advantage over the activate sludge process as MBBR does not require sludge recirculation nor a large sedimentation tank [2,3].…”
Section: Introductionmentioning
confidence: 99%